Application of Green Construction in Construction of the Bayung Lencir Toll Road - Rahmat; Prima Zola (Universitas Negeri Padang, 2025)
The implementation of Green Construction in infrastructure projects aims to reduce negative impacts on the environment and increase resource efficiency because every contusion project must have a negative impact on the environment, so the implementation of Green Construction is needed to reduce the negative impacts of construction activities. This study analyzes the implementation of the Green Construction concept in the construction of the Bayung Lencir - Tempino Toll Road Section 1. The research method includes collecting primary data through field observations and interviews with contractors and secondary data from various scientific references. The results of the study indicate that the implementation of Green Construction in this project includes energy efficiency, water conservation, environmental management, and the use of environmentally friendly materials. However, there are several obstacles in its implementation, such as technological limitations, lack of specific regulations, lack of stakeholder awareness, and limited funding for the use of environmentally friendly equipment. To overcome these challenges, stronger policy support, investment in green technology, and increased awareness and skills of the workforce related to Green Construction are needed. With more optimal implementation, this concept can be a sustainable solution in infrastructure development in Indonesia